Job-education match and professional mobility of selected BSHT graduates in a state university - Regatalio, Erly D. (College of Home Economics, University of the Philippines Diliman, 2018)
Abstract. Job-education match is an important concept in acquiring employment, promoting job satisfaction, and advancing professional mobility. It refers to the suitability or fit of one's tertiary education to the job one is currently employed in. The study investigated job-education match of selected Bachelor of Science in Home Technology (BSHT) graduates using the learned competencies derived from the syllabi-based objectives curriculum vis-a-vis the job-required competencies. It also differentiated the professional mobility of BSHT graduates whose job match with their education.